Light Weight Secure Key Generation Protocol with Hidden Generator Point using ECC - Moon, Ayaz Hassan; Iqbal, Ummer (Discoveries in Agriculture and Food Sciences, 2015)
Key generation and distribution is one of the most important primitive of any security framework. This is irrespective of using a symmetric or asymmetric cryptosystem. However, while securing a WSN, its resource constraint nature cannot be ignored. Therefore Elliptical Curve Cryptography (ECC) based solutions like Elliptical Curve Digital Signature algorithm (ECDSA), Elliptical Curve Diffie-Hellman (ECDH) are becoming more and more popular in comparison to other Public crypto system like RSA. In ECC, the Generator point is treated as a public parameter along with other domain parameters. This can make communication within the WSN vulnerable to man-in-the-middle attack. The attack can be thwarted by keeping the Generator point Private and still be able to establish a common Generator Point across communication parties .It will result in establishing a light weight secure key between a sender and a receiver and achieve other security primitives like generation of MAC and Node identification. This paper discusses and analyses the generation of Shared keys using 1 hidden generator point in comparison to 2- hidden point generator and the conventional ECDH method.